Efektivitas Lembar Balik terhadap Pengetahuan dan Sikap Ibu Hamil tentang Sunat Perempuan di Puskesmas Batujaya - Mulyana, Dede Sri; Karyanah, Karyanah (Universitas Malahayati, 2025)
ABSTRACT There is low knowledge of pregnant women about female circumcision, which can have an impact on their health and welfare as well as that of the child born. It is hoped that feedback as an educational medium can be an effective tool for conveying clear and interesting information. To determine the effectiveness of flip-sheet media on the knowledge and attitudes of pregnant women regarding female circumcision at the Batujaya Community Health Center. This research uses a pre-experimental design, which aims to evaluate the effect of the intervention provided (flip sheet media) on the knowledge and attitudes of pregnant women. The population in this study were pregnant women who visited the Batujaya Health Center. Samples were taken using sampling techniques in accordance with predetermined inclusion and exclusion criteria. Data obtained from the pretest and posttest were analyzed to determine the difference in the average knowledge and attitude scores of pregnant women before and after being given education. The average knowledge of pregnant women about female circumcision before being given education using flip sheets was 53.12. After being given education, the average knowledge increased to 84.90. The average attitude of pregnant women regarding female circumcision before being given education was 35.21, while after education it increased to 44.82. The results of statistical tests using the Wilcoxon test show a p value of 0.001, which means there is a significant influence of flip sheet media on increasing knowledge of pregnant women. that there is a significant average difference in the increase in knowledge scores and attitudes of pregnant women who are given health promotion about female circumcision using flip-sheet media. It is hoped that this research can be used as a literacy resource related to flip-sheet media and the topic of female circumcision, as well as encouraging further research to explore other educational methods that can improve people's knowledge and attitudes.Keywords: Flip sheet, Knowledge, Attitude, Pregnant women ABSTRAK Rendahnya pengetahuan ibu hamil tentang sunat perempuan, yang dapat berdampak pada kesehatan dan kesejahteraan mereka serta anak yang dilahirkan. embar balik sebagai media edukasi diharapkan dapat menjadi alat yang efektif untuk menyampaikan informasi yang jelas dan menarik. Untuk mengetahui efektivitas media lembar balik terhadap pengetahuan dan sikap ibu hamil tentang sunat perempuan di Puskesmas Batujaya. Penelitian ini menggunakan desain pre-experimental, yang bertujuan untuk mengevaluasi efek dari intervensi yang diberikan (media lembar balik) terhadap pengetahuan dan sikap ibu hamil. Populasi dalam penelitian ini adalah ibu hamil yang mengunjungi Puskesmas Batujaya. Sampel diambil dengan menggunakan teknik sampling yang sesuai dengan kriteria inklusi dan eksklusi yang telah ditentukan. Data yang diperoleh dari pretest dan posttest dianalisis untuk mengetahui perbedaan rata-rata skor pengetahuan dan sikap ibu hamil sebelum dan setelah diberikan edukasi. Rata-rata pengetahuan ibu hamil tentang sunat perempuan sebelum diberikan edukasi dengan media lembar balik adalah 53,12. Setelah diberikan edukasi, rata-rata pengetahuan meningkat menjadi 84,90. Rata-rata sikap ibu hamil tentang sunat perempuan sebelum diberikan edukasi adalah 35,21, sedangkan setelah edukasi meningkat menjadi 44,82. Hasil uji statistik menggunakan uji Wilcoxon menunjukkan nilai p Value 0,001, yang berarti ada pengaruh signifikan dari media lembar balik terhadap peningkatan pengetahuan ibu hamil. bahwa terdapat perbedaan rata-rata yang signifikan dalam peningkatan skor pengetahuan dan sikap ibu hamil yang diberikan promosi kesehatan tentang sunat perempuan dengan menggunakan media lembar balik. Penelitian ini diharapkan dapat digunakan sebagai sumber literasi yang berkaitan dengan media lembar balik dan topik sunat perempuan, serta mendorong penelitian lebih lanjut untuk mengeksplorasi metode edukasi lainnya yang dapat meningkatkan pengetahuan dan sikap masyarakat. Kata Kunci: Lembar Balik, Pengetahuan, Sikap, Ibu Hamil